Recent advances in the synthesis of α-amino ketones. Issue 3 (16th December 2020) - Allen, Lewis A. T.; Raclea, Robert-Cristian; Natho, Philipp; Parsons, Philip J.
Abstract : This review on α-amino ketone synthesis collates and evaluates developments made in this area over the past decade, with an extended discussion on functional group compatibility, resultant product substitution patterns, and medicinal applications. Abstract : Due to the importance of the amino ketone motif in synthetic and medicinal chemistry, the number of protocols developed in recent years has considerably increased. This review serves to collate and critically evaluate novel methodologies published since 2011 towards this high value synthon. The chapters are divided by the requisite functionality in the starting material, and an emphasis is placed on discussing functional group compatibility and resultant product substitution patterns. Throughout, applications to medicinal targets are highlighted and mechanistic details are presented, and we further provide a short outlook for future development and emerging potential within this area.